Assistance in Managing Efficacious Drinks Using Red Ginger Raw Material - Hilman Sholih; Wilarso; Miftahul Imtihan; Verry Surya Hendrawan; Hanifah Syayidah Lutfiyah (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
In managing and marketing the production of red ginger intonutritious drinks, there are often obstacles, starting from theprocess of selecting materials, production, packaging, to themarketing process. The purpose of this activity is to understandthe production process to sales. The method used is to provideassistance in managing red ginger production from production toonline marketing. From the results of the assistance carried outon the production of red ginger, 80% of the percentage isconsidered to provide a very good contribution to producersregarding their sales. As for the marketing process, it is donethrough social media or online digital marketing and the nearestwarung. The suggestion in the production of red ginger is thatthere needs to be an increase in more beautiful packaging models,to get the product's appeal to its customers.